Clinical significance of cerebral microbleeds locations in CADASIL with R544C NOTCH3 mutation. - Jung Seok Lee; Chul-Hoo Kang; Sukh Que Park; H Alex Choi; Ki-Bum Sim (PLoS ONE, 2015)
Although cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common single-gene disorder of cerebral small blood vessels caused by NOTCH3 mutations, little has been described about the variation in the clinical findings between its underlying types of mutations. In particular, the presence of cerebral microbleeds (CMBs) has been an increasingly recognized magnetic resonance imaging finding in CADASIL, but their clinical significance is not clear. The purpose of this study is to assess whether CMBs are associated with symptomatic stroke in the CADASIL patients with R544C mutation and to compare the cerebral distribution of CMBs between CADASIL patients with and without symptomatic stroke.This is a cohort study of patients who were diagnosed with genotype-confirmed R544C-mutation CADASIL. Primary neurologic symptoms were recorded. Symptomatic strokes were defined as transient ischemic attack, ischemic strokes and hemorrhagic strokes. CMBs were defined as focal areas of round signal loss on T2*-weighted gradient echo planar images with a diameter of less than 10 mm. The locations of CMBs were divided into lobar, basal ganglia, thalamus, brain stem and cerebellum. Multiple logistic regressions were performed to identify the epidemiologic or vascular risk factors associated with symptomatic stroke in patients with CADASIL.Among total of 51 subjects in this cohort, CMBs were present in 20 of 32 patients (64.5%) in the symptomatic stroke-group and in 8 of 19 patients (42.1%) in the non-stroke group (p = 0.16). CMBs were observed more frequently in the basal ganglia (p<0.001) and the cerebellum (p<0.018) in the symptomatic stoke group compared to the non-stroke group. The mean number of CMBs was significantly higher in the symptomatic stroke group (15.4±18.0 lesions per patients with CMBs) versus those without symptomatic stroke (3.3±3.0 lesions per patients with CMBs) (p = 0.003). Hypertension was an independent risk factor for symptomatic stroke in CADASIL (p = 0.014). It was independently associated with CMBs locations as basal ganglia (p = 0.016), thalamus (p = 0.010), brainstem (p = 0.044), and cerebellum (p = 0.049). However, It was not independently associated with CMBs on lobar lesion (p = 0.152).In this study hypertension was an independent predictor of CMBs presence in specific brain locations, as well as symptomatic stroke in the CADASIL patients. The distribution and burden of CMBs might be a clinically useful marker for the risk of symptomatic stroke. However, further prospective studies on the relationship between CMBs distribution and symptomatic stroke are required in order to support these preliminary findings.